(2-{[1,1-Bis(hydroxymethyl)-2-oxidoethyl]iminomethyl}-4-chlorophenol ato-kappa N-3,O,O `)dibutyltin(IV) - Reisi, R.; Misran, M.; Lo, K.M.; Ng, S.W. (International Union of Crystallography, 2010)
The Schiff base ligand in the title compound, [Sn(C4H9)(2)(C11H12ClNO4)], chelates to the Sn atom through the two deprotonated O atoms, as well as through the N atom, to confer an overall cis-C2SnNO2 trigonal-bipyramidal geometry at tin [C-Sn-C = 130.3 (1)degrees]. The hydroxy groups engage in O-H center dot center dot center dot O hydrogen bonding with the O atoms of adjacent molecules, generating a chain running along the c axis.